Professional'nyj kommerceskij sport v Rossii: istorija i sovremennsot' - Pocinkin, A. V. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The contradictions in the knowledge of professional commercial sports as an object of the research have allowed the author of the article to concretize the problem through the questions: "What regularities and tendencies of the process of becoming and development of the professional commercial sports in Russia?", "What are its further prospects?", "What should the control system of it be like?". This article is devoted to the partial decision of the given questions.